MAPPING THE CARBON SEQUESTRATION OF MATURE TREES FOR LANDSCAPE PLANNING AND MANAGEMENT USING GEOGRAPHIC INFORMATION SYSTEM (GIS): A CASE STUDY OF HOSPITAL GERIK, PERAK - Norsyazlin Mohd Rosli; Ruwaidah Borhan; Nur Shaffiqa Muhammad Soffian; Amelia Ahmad (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
This paper seeks to address the existing research gap by introducing a novel database in the context of mapping the carbon sequestration of mature trees, utilizing Geographic Information System (GIS) for enhanced landscape planning and management strategies. While previous studies have explored the use of GIS in landscape planning, limited attention has been directed towards its application in mapping the carbon sequestration of mature trees, particularly in health facilities. One objective of this study is to provide a carbon sequestration database that consists of spatial and attributes data that can be used by the management of landscape planning for monitoring works and become more aware of existing trees that can give more benefit to the environment and climatic change globally. The methodology consists of presenting the sequential method of developing the database with spatial and attribute data using Entity-Relationship Diagram (ERD), and performing spatial analysis and carbon sequestration of mature trees map at Hospital Gerik, Perak using GIS software. The analysis shows the total amount of carbon sequestration area for 14 species of trees and 49 trees with a range of Diameter Breast at Height (DBH) between 0.5 cm to 450cm and a range height between 0.6m to 20m height. This paper provides valuable insights for health facility management, highlighting the environmental value of the mature trees currently located within the vicinity of their buildings. Depending on spatial maps of carbon sequestration, the recommendations and implications for improving the landscape planning and management at Hospital Gerik are discussed in comprehensively.